Habitat use and diet preference of extralimital giraffes in the Kgalagadi Transfrontier Park - Viljoen, Storme (Department of Biological Sciences, 2015)
Extralimital giraffe introductions in the south-western region of Kgalagadi Transfrontier Park, South Africa, may result in changes to the vegetation structure for the region through overutilization of two keystone tree species in the area. In the areas where giraffe density was highest, I determine the relative abundance of giraffe; their diet preference and the potential reasons for this preference. Using both spoor and dung counts as indicators of giraffe presence, transects were carried out over approximately 20 km of the Auob River. Percentage occurrence was plotted onto a map of the river, along with the location of boreholes that supply the only surface water. Little trend could be seen, although occurrence appeared slightly higher near boreholes. The two trees that most commonly occur in the Auob duneveld, Acacia erioloba and Acacia haematoxylon, were examined for nutritional content, and both chemical and physical defences - all of which are thought to affect herbivore selection. Stable isotope analysis and linear mixing model were used to determine the proportion of each species in the diet of giraffe using the leaves of both species and giraffe dung. The majority of the giraffe's diet consists of A. haematoxylon (mean = 79 %, s.d. = 20.5 %) despite having less crude protein and similar condensed tannin content. Relative lack of physical defences appears to encourage giraffes to exploit A. haematoxylon, which has shorter, weaker thorns. Without management intervention, A. haematoxylon could suffer selective mortality through the impacts of giraffe browsing, resulting in a loss of species and structural diversity of the landscape.